2020
DOI: 10.1037/mot0000163
|View full text |Cite
|
Sign up to set email alerts
|

The MASC: A novel multidimensional measure of self-control.

Abstract: The current study seeks to create a brief survey measure of self-control that differentiates perceived capacity from internal and external motivation. Items were adapted from the Brief Self-Control Scale (BSCS; Tangney, Baumeister, & Boone, 2004) and administered through 2 online surveys to 347 students and 1 online survey to 192 participants from Amazon Mechanical Turk. The Multidimensional Assessment of Self-Control showed strong evidence for the reliability of test scores and the validity of the interpretat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 52 publications
(60 reference statements)
0
2
0
Order By: Relevance
“…On the level of measurement, the idea that different theoretical notions need to be considered is also gaining traction. Some researchers have suggested that the Self‐Control Scale (Tangney et al., 2004) is not uni‐ but multidimensional (e.g., Hagger et al., 2021; Lindner et al., 2015; see also Papova & Corbin, 2020). One distinction that emerged refers to the ability to initiate actions conducive to goal attainment versus the ability to stop actions that are maladaptive (de Boer et al., 2011; de Ridder et al., 2011).…”
Section: Conceptual Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…On the level of measurement, the idea that different theoretical notions need to be considered is also gaining traction. Some researchers have suggested that the Self‐Control Scale (Tangney et al., 2004) is not uni‐ but multidimensional (e.g., Hagger et al., 2021; Lindner et al., 2015; see also Papova & Corbin, 2020). One distinction that emerged refers to the ability to initiate actions conducive to goal attainment versus the ability to stop actions that are maladaptive (de Boer et al., 2011; de Ridder et al., 2011).…”
Section: Conceptual Challengesmentioning
confidence: 99%
“…Integrating motivation and ability would also advance trait self‐control measurement. Prominent self‐report measures, such as the Self‐Control Scale (Tangney et al., 2004), include items that refer to ability‐related (e.g., “I am good at resisting temptation”) and motivational (e.g., “I am not easily discouraged”) aspects but do not separate the two, for example, in the form of specific subscales (but see Papova & Corbin, 2020). Another prominent way to measure trait self‐control is to use behavioral inhibition tasks such as the Stroop (1935) or the Flanker task (Eriksen & Eriksen, 1974).…”
Section: Conceptual Challengesmentioning
confidence: 99%